2001
DOI: 10.1080/11250000109356379
|View full text |Cite
|
Sign up to set email alerts
|

Is GABA present in the nervous system of acoel plathelminthes? An electron immunocytochemical study

Abstract: Our immunocytochemical investigation positively identified for the first time at the ultrastructural level the presence of GABA-ir neurones and terminals in the nervous system of a plathelminth, the acoel Symsagittifera psammophila. The gold particles are localized on clear vesicles (about 30-60 nm wide) of somata and terminals prevalently distributed in the neuropile area near the statocyst. GABA-ir vesicles are also present at neuromuscular junctions. The significance of this finding in a lower invertebrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The different types of neurotransmitter present in the eyespots of P. dumerilii and S. roscoffensis could explain the resulting structural and functional differences of the photoreceptors in the two species. Similarly in S. roscoffensis, the statocyst, the organ of gravity in acoels, is devoid of cholinergic cells, not surprisingly since in Symsagittifera psammophila, Bedini et al (2001) revealed GABA-immunoreactivity in the area near the statocyst, using immunogold labelling. Thus, we hypothesize that GABAergic fibres might innervate the statocyst in S. roscoffensis, but further analysis of the GABAergic pattern in S. roscoffensis is required.…”
Section: Intact Adultsmentioning
confidence: 95%
“…The different types of neurotransmitter present in the eyespots of P. dumerilii and S. roscoffensis could explain the resulting structural and functional differences of the photoreceptors in the two species. Similarly in S. roscoffensis, the statocyst, the organ of gravity in acoels, is devoid of cholinergic cells, not surprisingly since in Symsagittifera psammophila, Bedini et al (2001) revealed GABA-immunoreactivity in the area near the statocyst, using immunogold labelling. Thus, we hypothesize that GABAergic fibres might innervate the statocyst in S. roscoffensis, but further analysis of the GABAergic pattern in S. roscoffensis is required.…”
Section: Intact Adultsmentioning
confidence: 95%